Comparison between Vapocoolant Spray and Eutectic Mixture of Local Anesthetics Cream in Reducing Pain during Spinal Injections - Riyadh Firdaus; Besthadi Sukmono; Annemarie Chrysantia Melati; Berial Dewin Marzaini (Anesthesiology Research and Practice)
Background. Eutectic mixture of local anesthetics (EMLA) cream is often used for local anesthesia during spinal injections. However, this agent has delayed onset of action while vapocoolant spray serves more advantages. The vapocoolant spray containing ethyl chloride has fast onset and is safe, low cost, and widely available. This study aimed at comparing the effectiveness of vapocoolant spray and EMLA cream in reducing pain for spinal injections. Methods. This was an experimental study on 94 subjects with 47 subjects treated with EMLA cream and 47 subjects treated with vapocoolant spray. The effectiveness of anesthesia was assessed by using Numeric Pain Rating Scale (NPRS) and patient movement during the surgery. Results. This study found that the pain scale was NPRS 0 (0–3) for the EMLA group and NPRS 0 (0–4) for the vapocoolant spray group. There was no significant difference between two groups for pain scale according to the Mann–Whitney U test. For patient movement, the movement was reported only in one (2.1%) patient in the EMLA group and one (2.1%) patient in the vapocoolant spray group. Based on Fisher’s test, there was no significant difference between the two groups for patient movement. Conclusions. Both EMLA cream and vapocoolant spray were equally effective in reducing pain during spinal injection. There was no difference in degree of pain reduction and patient movement between the EMLA cream group and the vapocoolant spray group during spinal injection.